Transparansi Informasi Hukum melalui Jaringan Dokumentasi dan Informasi Hukum (JDIH) Kemenkumham Kalteng - Muhamad Taufik Wahyudi; Risma Yana; Aisyah Andriani; Noor Ulfa Amelia; Amelia Fitria Wulandari; Reza Noor Ihsan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the implementation of legal information transparency through the Legal Documentation and Information Network (JDIH) of the Ministry of Law and Human Rights of Central Kalimantan. The main focus of the research is to explore the aspects of document completeness, information accessibility, display quality, depth of information, and compliance with public information transparency standards. Using normative juridical research methods with legislative and conceptual approaches, this study analyzes secondary data related to legal information transparency. The results of the study show that the JDIH of the Ministry of Law and Human Rights of Central Kalimantan has implemented a legal documentation and information system that is oriented towards user convenience, although it still faces several challenges in information management. The system provides various types of legal documents and implements a participatory approach in improving the quality of services. Nevertheless, continuous development is still needed in the aspects of document updating, information organization, and system stability to optimize the transparency of legal information in Central Kalimantan.